Pulsed terahertz spectroscopy of DNA, bovine serum albumin and collagen between 0.1 and 2.0 THz - Markelz, A. G.; Roitberg, A.; Heilweil, E. J. (Chemical Physics Letters, 2000)
We report the first use of pulsed terahertz spectroscopy to examine low-frequency collective vibrational modes of biomolecules. Broadband absorption increasing with frequency was observed for lyophilized powder samples of calf thymus DNA, bovine serum albumin and collagen in the 0.06-2.00 THz (2-67 cm(-1)) frequency range, suggesting that a large number of the low-frequency collective modes for these systems are IR active. Transmission measurements at room temperature showed increasing FIR absorption with hydration and denaturing. (C) 2000 published by Elsevier Science B.V. All rights reserved.
Keywords: b-dna; Chemistry; films; modes; Physics; proteins